You can't spell America without me : the really tremendous inside story of my fantastic first year as President Donald J. Trump (a so-called parody) /: the really tremendous inside story of my fantastic first year as President Donald J. Trump (a so-called parody). (2017) - Baldwin, Alec, 1958-; Andersen, Kurt, 1954-
No abstract available